Augmented Communication The Effect of Digital Devices on Face-to-Face Interactions - Pinner, Richard S. (Springer International Publishing : Imprint: Palgrave Pivot, 2019)
This book explores the ways in which handheld networked devices can be used to enhance and augment interpersonal communication. The author examines in depth how the addition of visual and multimodal input, access to online search engines and the inclusion of participants from distant geographical locations (either synchronously or asynchronously) affects our face to face interactions. Presenting research data from several years of autoethnographic observation, this balanced work reveals the consequences, both positive and negative, of technology-dependent forms of discourse. In doing so, this sociolinguistic perspective fills a gap in the current literature and indicates possible future directions for the study of augmented communication. It will appeal in particular to students and scholars of sociolinguistics, applied linguistics and digital humanities. Richard S. Pinner is Associate Professor in the Department of English Literature at Sophia University, Japan.